1981
DOI: 10.1002/jsscb.380170404
|View full text |Cite
|
Sign up to set email alerts
|

The role of glycoconjugates in metastatic melanoma blood‐borne arrest and cell surface properties

Abstract: The role of glycoconjugates in cell surface and blood-borne implantation properties of murine metastatic melanoma sublines of low (B16-F1) or high (B16-F10) potential to colonize lungs was investigated by treating melanoma cells with the antibiotic tunicamycin. This drug prevents glycosylation of glycoproteins by inhibiting the formation of lipid-linked oligosaccharide precursors. The degree of tunicamycin-mediated modifications in glycoproteins was assessed by monitoring the decrease in cell surface sialogala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…As other authors have found [22,34,33], tumor cell adherence to ECM was more efficient than attachment to endothelial cells. The percentages of tumor cells bound to endothelial cell monolayers and to ECM were similar to those obtained by Vlodavsky et al [23].…”
Section: Discussionsupporting
confidence: 54%
“…As other authors have found [22,34,33], tumor cell adherence to ECM was more efficient than attachment to endothelial cells. The percentages of tumor cells bound to endothelial cell monolayers and to ECM were similar to those obtained by Vlodavsky et al [23].…”
Section: Discussionsupporting
confidence: 54%
“…For example, Irimura and Nicolson (138) found that treatment of B16 melanoma cells with tunicamycin, an inhibitor of glycoprotein synthesis, altered their arrest pattern in vivo following i.v. injection and impaired their ability to produce lung metastates.…”
Section: B Experimental Models For Studying the Behavior Of Circulatmentioning
confidence: 99%
“…This effect has been correlated with the presence of certain surface sialoglycoproteins (8,9,11). However, since tunicamycin is known to be toxic at least for most tumor cells (12,13), the significance of this finding remains unclear.…”
mentioning
confidence: 92%
“…In assays for blood-borne metastasis, treatment of B16 murine melanoma cells with tunicamycin, an inhibitor of the biosynthesis of N-linked glycoproteins, appeared to abrogate pulmonary colonization in syngeneic mice (8)(9)(10). This effect has been correlated with the presence of certain surface sialoglycoproteins (8,9,11).…”
mentioning
confidence: 99%